Sistem Informasi Penjualan di Cafe Sungrilla Outbound and Camping Berbasis Web - Valda Khatami Inayyah; Surmayanti (Universitas Putra Indonesia YPTK Padang, 2024)
Recently, the field of knowledge and technology has undergone rapid advancements, especially in the realm of computers and smartphones. Information technology is no longer just expected to serve as a tool for assisting and streamlining company operations; it has evolved into a strategic component for maintaining employee performance. In this regard, information systems utilizing computer resources are employed to aid in processing information according to a company's requirements. Recognizing the significance of this for a company, the author conducted research on the information system needs at Cafe Sungrilla Outbound and Camp Padang. Consequently, to fulfill the demand for an information system, the author conducted an analysis and designed an information system for the data processing of reservations, involving the collection of data and study of relevant theories associated with the reservation process